Daya Tarik Visual Karakter pada Figur Anime: Studi Kasus Cosplayer di Surabaya - Nugraha Nugraha; Hedi Amelia Bella Cintya; Ariri Riska Orelia Nor Adha; Izzati Aulya Akhiroh Prastyo (Lembaga Pengembangan Kinerja Dosen, 2026)
This study aims to analyze the visual appeal of anime characters through a case study of cosplayers in Surabaya. The focus of this research is to identify the factors that motivate cosplayers to idolize anime characters and to describe the visual elements that contribute to the formation of such appeal. This study employs a qualitative approach using observation, interviews, documentation, and questionnaire distribution to 30 active cosplayers aged 18–20 who are members of cosplay communities in Surabaya. The collected data were analyzed using Charles Sanders Peirce’s semiotic approach, which emphasizes the relationship between sign, object, and interpretant in the process of visual meaning-making. The results indicate that the appeal of anime characters is not solely influenced by visual aspects but also by emotional attachment formed through character representation. Specifically, facial features (66.7%) and body gestures (33.3%) are the dominant factors influencing cosplayers’ preferences, compared to other visual elements such as color, costume, and hair details. The semiotic analysis reveals that visual elements in cosplay function as a system of signs that represent character identity while simultaneously constructing aesthetic, emotional, and narrative meanings for the audience.